The evolutionary history of Antirrhinum in the Pyrenees inferred from phylogeographic analyses - Liberal, Isabel M (BioMed Central, 2014)
BACKGROUND: The origin and colonisation history after the Quaternary ice ages remain largely unresolved for many plant lineages, mainly owing to a lack of fine-scale studies. Here, we present a molecular phylogeny and a phylogeographic analysis of Antirrhinum, an important model system in plant biology, in the Pyrenees range. Our goal was to reconstruct the evolutionary and colonisation history of four taxa endemic to this region (A. majus subsp. majus, A. majus. subsp. striatum, A. molle, and A. sempervirens) by using a dense sampling strategy, with a total of 452 individuals from 99 populations whose collective distribution spans nearly the entirety of the Pyrenees and adjacent mountains. RESULTS: Phylogenetic and phylogeographic analyses of the sequences of two plastid (trnS-trnG and trnK-matK) regions revealed the following: (i) historical relationship between the Pyrenees and Iberia (but not with the Alps); (ii) the long persistence of populations in the Pyrenees, at least since the Late Pleistocene; (iii) three different colonisation histories for populations from the Western, Central, and Eastern Pyrenees; (iv) the deep phylogeographic separation of the eastern and western populations; and (v) the colonisation of southern France from the Eastern Pyrenees. CONCLUSIONS: The present study underlines the enormous influence of the glacial history of the mountain ranges on the current configuration of intra- and inter-specific genetic diversity in Antirrhinum, as well as the importance of periglacial areas for the survival of species during glacial periods of the Quaternary.